Technical Perspective IronFleet Simplifies Proving Safety and Liveness Properties. - Schneider, Fred B. (Communications of the ACM, 2017)
An introduction is presented to an article that describes the safety and liveness properties of the IronFleet system software for distributed services including replication support and a shared key-value store.